Antihypertension drugs in prevention of cognition disorder and dementia: focus on calcium channel blockers and diuretics - O. D. Ostroumova; M. S. Chernyaeva (Кардиоваскулярная терапия и профилактика, 2018)
Arterial hypertension is associated with elevated risk of cognition decline and vascular dementia development, as the Alzheimer disease development. Therefore, antihypertension therapy might be of preventive value. The review is focused on literary data that witness on, despite controversial, evidence of cerebroprotective action of the range of antihypertension medications. Especially, dihydropyridine calcium antagonists, diuretics and some blockers of renin-angiotensin-aldosterone system. These act not only via blood pressure decrease, but due to additional specific neuroprotective mechanisms. This makes it to consider calcium antagonists and diuretics as a major component of systemic hypertension management, incl. elderly and senile patients, aiming to prevent cognition decline and dementia of various types development.Nitrendipine, among the calcium channels antagonists, and indapamide among diuretics have acquired the broadest evidence that points on their cerebroprotective properties.